Child-Friendly School-Based Bullying Prevention Model Through the Role of PAI Teachers at SMP Negeri 2 Kartasura - Zahra, Nindifia Al; Maksum, Muh.Nur Rochim (Universitas Muhammadiyah Surakarta, 2025)
This study aims to describe in depth the bullying phenomenon that occurs at SMP Negeri 2 Kartasura. The focus of the research is directed at efforts to understand the meaning of bullying, identify the forms of bullying experienced by students, and analyze the factors that cause bullying in the school environment. In addition, this study also examines the role of Islamic Religious Education (PAI) teachers in preventing and dealing with bullying as part of student character formation and the creation of a safe and child-friendly school environment. This study uses a qualitative approach with a type of field research through a phenomenological approach. This approach was chosen to gain a deeper understanding of the experiences and social realities that occur in schools. The main data source came from PAI teachers, while supporting data was obtained from parents and school officials. Data collection techniques were carried out through in-depth interviews, participatory observations, and documentation. The data obtained were analyzed through the stages of data reduction, data presentation, and conclusion drawing to find relevant patterns related to bullying behavior and the role of PAI teachers in its prevention. The results of the study show that bullying at SMP Negeri 2 Kartasura still occurs in various forms, especially verbal, economic, and relational bullying, as well as in certain situations physical bullying. Bullying behavior is influenced by family background, social environmental pressure, and emotional instability of students in adolescence. PAI teachers play an important role in bullying prevention efforts through character building, role modeling, individual and group guidance, and integrating religious values in the learning process and character strengthening activities. The findings of this study provide an applicative value for schools in strengthening the Child-Friendly School program through an integrated and sustainable approach to character education.